Adult spinal opioid receptor μ1 expression after incision is altered by early life repetitive tactile and noxious procedures in rats. Issue 4 (28th February 2018) - van den Hoogen, Nynke J.; van Reij, Roel RI; Patijn, Jacob; Tibboel, Dick; Joosten, Elbert A. J.
ABSTRACT: Clinical and experimental data suggests that noxious stimulation at critical stages of development results in long‐term changes on nociceptive processing in later life. Here, we use an established, well‐documented rat model of repetitive noxious procedures closely mimicking the clinical situation in the NICU. In order to understand molecular changes underlying the long‐term consequences of repetitive stimulation of the developing nociceptive system the present study aims to analyze the presence of the µ‐opioid‐receptor‐1 (OPRM1). Neonatal rats received either four needle pricks per day in the left hind‐paw from postnatal day 0–7 as a model of procedural pain in infancy. Control pups were handled in the same way but were instead tactile stimulated, or were left undisturbed. At the age of 8 weeks, all animals received an ipsilateral hind‐paw incision as a model for post‐operative pain, and mechanical sensitivity was tested at multiple time‐points. Before, and 1 or 5 days post‐incision, spinal cord tissue was collected for immunostaining of opioid receptor OPRM1. Semi‐quantitative immunocytochemical analysis of superficial laminae in lumbar spinal dorsal horn revealed that: (1) early life repetitive tactile or noxious procedures do not alter baseline levels of OPRM1 staining intensity and (2) early life repetitive tactile or noxious procedures lead to a decrease in OPRM1 staining intensity 5 days after incision in adulthood compared to undisturbed controls. We conclude that early life repetitive tactile or noxious procedures affect the intensity of OPRM1‐immunoreactivity in the lumbar superficial spinal cord dorsal horn after adulthood injury, without affecting baseline intensity. © 2018 The Authors. Developmental Neurobiology Published by Wiley Periodicals, Inc. Develop Neurobiol 78: 417–426, 2018